Clinical Case of Rendu–Osler Syndrome: The Role of Pharmaceutical Care in Optimizing Pharmacotherapy - Yevdokymova, Yelyzaveta; Temirova, Olena; Andrushchenko, Iryna; Khaitovych, Mykola (The Ukrainian Scientific Medical Youth Journal, 2026)
Introduction. Rendu-Osler syndrome, also known as hereditary hemorrhagic telangiectasia, is an orphan genetic disorder characterized by multisystem vascular involvement and recurrent bleeding, most commonly epistaxis. Frequent nosebleeds can lead to chronic iron-deficiency anemia and significantly impair patients' quality of life. Aim. This study aimed to substantiate the role of pharmaceutical care in ensuring rational and safe use of medications based on a clinical case of Rendu-Osler syndrome. Materials and Methods. A retrospective analysis of a patient's medical records for Rendu-Osler syndrome for the period 2022-2025 was conducted using the case method. A clinical and pharmaceutical analysis of the prescribed pharmacotherapy was conducted, along with an assessment of potential drug interactions using the DrugBank Online database and a retrospective review of literature sources in PubMed and Cochrane Library. Results. The patient presented with recurrent episodes of epistaxis, anemic syndrome, and the need for interventional treatment. The use of tranexamic acid contributed to a reduction in the intensity and frequency of nosebleeds. The clinical and pharmaceutical analysis helped identify potential risks of drug interactions and formulate recommendations to improve the safety of pharmacotherapy, including monitoring of coagulation parameters and iron status with the possibility of iron deficiency correction. Conclusions. The presented clinical case demonstrates the importance of a comprehensive approach to managing patients with Rendu-Osler syndrome. Pharmaceutical care, which encompasses clinical and pharmaceutical analysis of pharmacotherapy, safety monitoring, and patient education, is an essential tool for optimizing treatment and improving clinical outcomes.